Pengaruh Gaya Kepemimpinan dan Motivasi Kerja terhadap Kinerja Karyawan di Dinas Kesehatan Bantul - Hodiri Adi Putra; Nor Wijayanti; Edi Jumadi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Organizations must pay attention to factors that can increase employee performance, including work motivation and leadership styles that can increase work enthusiasm while creating a professional work attitude. The aim of this research is to determine the influence of leadership style and work motivation on employee performance at the Bantul District Health Service. This research method is a quantitative model, with a cross sectional approach. The sample used was 51 people, selected based on Purposive Sampling. Data were analyzed using multiple linear regression. The results of research using the Kendall Tau test on the leadership style variable on employee performance obtained a sig. (2-tailed) of 0.004 < 0.05. The results of the work motivation test on employee performance obtained a sig. (2-tailed) of 0.000 < 0.05. Based on the results of simultaneous Ordinal Regression Analysis, leadership style and work motivation on employee performance obtained a sig value of 0.000. Conclusion. There is a significant and significant influence of leadership style on employee performance, there is an influence of work motivation on employee performance, simultaneously there is an influence of leadership style and work motivation on employee performance.